Iodine and pregnancy – a UK cross-sectional survey of dietary intake, knowledge and awareness. Issue 1 (26th May 2015) - Combet, E.; Bouga, M.; Pan, B.; Lean, M. E. J.; Christopher, C. O.
Abstract : Iodine is a key component of the thyroid hormones, which are critical for healthy growth, development and metabolism. The UK population is now classified as mildly iodine-insufficient. Adequate levels of iodine during pregnancy are essential for fetal neurodevelopment, and mild iodine deficiency is linked to developmental impairments. In the absence of prophylaxis in the UK, awareness of nutritional recommendations during pregnancy would empower mothers to make the right dietary choices leading to adequate iodine intake. The present study aimed to: estimate mothers' dietary iodine intake in pregnancy (using a FFQ); assess awareness of the importance of iodine in pregnancy with an understanding of existing pregnancy dietary and lifestyle recommendations with relevance for iodine; examine the level of confidence in meeting adequate iodine intake. A cross-sectional survey was conducted and questionnaires were distributed between August 2011 and February 2012 on local (Glasgow) and national levels (online electronic questionnaire); 1026 women, UK-resident and pregnant or mother to a child aged up to 36 months participated in the study. While self-reported awareness about general nutritional recommendations during pregnancy was high (96 %), awareness of iodine-specific recommendations was very low (12 %), as well as the level of confidence of how to achieve adequate iodine intake (28 %). Median pregnancy iodine intake, without supplements, calculated from the FFQ, was 190 μg/d (interquartile range 144–256μg/d), which was lower than that of the WHO's recommended intake for pregnant women (250 μg/d). Current dietary recommendations in pregnancy, and their dissemination, are found not to equip women to meet the requirements for iodine intake.